Neuromuscular and motor patterns in breaststroke technique - Conceição, Ana (2021)
Abstract – Te aim of this study was to analyze the inter-temporal neuromuscular and motor patterns in breaststroke technique. Five national level male swimmers performed 200 m breaststroke at maximal eﬀort. Electromyography data onbiceps brachii, deltoid anterior, pectoralis major and triceps brachiiwere analysed. Te relative duration of active and non-active phase and the average rectifed value for the neuromuscular patterns were recorded. Te swim bouts were videotaped in sagittal plane with a pair of cameras and the Teme software 5.0 was used toanalyse the detected patterns in each swimmer. Te neuromuscular pattern revealed that by the average rectifed value the biceps brachiiand triceps brachiiwere increased at the end of the test for swimmers 1 and 5, while biceps brachii, deltoid anteriorand pectoralis majorwere increased for swimmers 2 and 4. Diﬀerent motor patterns between cycles, and between swimmers were observed.We found similarities between the swimmers, adjusting their style to the technical model. Te absence of a neuromuscular pattern for all swimmers could be related to diﬀerent technical models used by each swimmer, as presented in the motor patterns. Tese fndings suggested that each swimmers adapted their own motor and neuromuscular pattern in a unique and distinct way